Peran Komunitas Seni dalam Pembentukan Identitas Penggiat Seni pada Generasi Muda: Studi Kasus Gambang Semarang Art Company - Andini, Dila Putri; Alimi, Moh Yasir (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In the midst of modernization, many traditional arts are endangered due to lack of interest from the younger generation. Globalization has brought challenges to the preservation of traditional arts, including efforts to maintain cultural identity in Indonesia. This research examines the role of the Gambang Semarang Art Company (GSAC) Community in the formation of art activist identity in the younger generation through a qualitative case study approach. The research aims to understand the motivation of the younger generation to join GSAC, the activities organized by the community, as well as the role of the community in shaping the identity of art activists in the younger generation. The research findings show that: (1) young people are motivated to join GSAC because of their love for traditional arts and the need for a supportive community; (2) in order to preserve Gambang Semarang, GSAC organizes various creative activities, including rehearsals, collaboration with schools, and participation in festivals; (3) GSAC plays three important roles in helping to shape the identity of art activists, namely as a forum for identity negotiation, an agent of cultural adaptation, and a space for social interaction. In the face of the challenges of globalization, this research makes a significant contribution to efforts aimed at the preservation of arts and culture. By showing how local arts groups can evolve into dynamic centers of cultural identity, this research also uses theories of symbolic interactionism and social identity.